-3(2x-5)+7=(3-x)

Simple and best practice solution for -3(2x-5)+7=(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2x-5)+7=(3-x) equation:


Simplifying
-3(2x + -5) + 7 = (3 + -1x)

Reorder the terms:
-3(-5 + 2x) + 7 = (3 + -1x)
(-5 * -3 + 2x * -3) + 7 = (3 + -1x)
(15 + -6x) + 7 = (3 + -1x)

Reorder the terms:
15 + 7 + -6x = (3 + -1x)

Combine like terms: 15 + 7 = 22
22 + -6x = (3 + -1x)

Remove parenthesis around (3 + -1x)
22 + -6x = 3 + -1x

Solving
22 + -6x = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
22 + -6x + x = 3 + -1x + x

Combine like terms: -6x + x = -5x
22 + -5x = 3 + -1x + x

Combine like terms: -1x + x = 0
22 + -5x = 3 + 0
22 + -5x = 3

Add '-22' to each side of the equation.
22 + -22 + -5x = 3 + -22

Combine like terms: 22 + -22 = 0
0 + -5x = 3 + -22
-5x = 3 + -22

Combine like terms: 3 + -22 = -19
-5x = -19

Divide each side by '-5'.
x = 3.8

Simplifying
x = 3.8

See similar equations:

| 103-4x=4x+7 | | T=3m+3z | | -3(2x-5)7=(3-x) | | x+(x+3)=23 | | 3x-2=80 | | x/0.6=9.3 | | 6x+12-7=41 | | 6k-4=2k+8 | | -2+3y=12 | | 4(11x+2)-17=23x-2 | | 4x^2-16=8 | | 139144= | | 8x-(x+3)=11 | | 6(3f-10)=30 | | 80+y^2=0 | | (a-4)*(a+4)= | | 6x+12=-58-8x | | 2x-6=-x+15 | | 3x+9x+10=13 | | 5u(2u+3)-2u(u-7)= | | 2x+127=12x-13 | | 3c^2-3c=4c | | 9-7x=84-42x | | 2x-5x=10 | | 5x^2-55x+20=0 | | 10-7x=103-28x | | x^2-16=-13 | | 112-7x=38+17 | | 140-3x=33x+20 | | 25x^2+11=15 | | 3x^2+18x-25=0 | | x^2-7x=7 |

Equations solver categories